Can we predict individual investors’ behavior in stock markets? A psychological approach - Pascual-Ezama, David; UNIVERSIDAD COMPLUTENSE DE MADRID (2013)
Understanding financial markets and investors’ behavior is one of the biggest objectives in finance. However, most of the research obtained conclusions about individual investors, but they are not studying real individual investors’ behavior: they analyzed stock price evolution or used aggregate investor data that essentially belongs to founds and big investors. Psychology has improved financial knowledge and solved many of those financial limitations. Because of that, we decided to apply one of the most valid psychological models to study human behavior, in order to better understand real individual investors’ behavior: the Theory of Planned Behavior (TPB; Ajzen, 1991). The model was applied to 127 real investors obtained by the “snowball” technique. According to results, TPB seems to be a good model to understand individual investor’s behavior, while explaining 63% of the investments’ intentions and 48% of the investments’ behavior.